Interfacial Behavior of Low- and High-Molecular Weight Compounds vs. Temperature and Confinement Effects - V. M. Gun'ko; V. V. Turov; V. I. Zarko; O. V. Goncharuk; O. S. Remez; R. Leboda; J. Skubiszewska-Zięba (Хімія, фізика та технологія поверхні)
The interfacial and temperature behavior of water, n-decane, decanol, poly(dimethylsiloxane) (PDMS) bound to nanooxides initial or after high-pressure cryogelation and silica gels was analyzed using low-temperature 1H NMR spectroscopy (applied to static samples to observe only mobile adsorbates), differential scanning calorimetry (DSC), thermoporometry and quantum chemical methods. Both NMR and DSC results demonstrated that during heating of frozen samples a fraction of organics or PDMS remained frozen at temperature higher than the melting point of bulk liquid and a fraction of any adsorbate remained unfrozen upon cooling at temperature lower than the freezing point. These effects depend on the type of an adsorbate and the pore sizes of an adsorbent. Broadening of freezing/melting temperature range is observed for PDMS or decane confined in pores of silica gel or voids between nanoparticles in fumed nanooxides. This effect is minimal for silica gel Si-100 with broad mesopores.